Study on mechanism of lubricant additives for alternative refrigerants - 赵蕾; 刘咸定 (Zhileng xuebao)
Based on literature reviewing and experiment studying, the features of various lubricants for HFCs refrigerants are explained and their faults are analyzed. It is pointed out that the faults can be compensated by suitable additives. The mechanism of various additives is studied and experiments are carried out to test the function of polarized lubricant additive PROA. Test results indicate that PROA can better system lubricity and prolong the longevity of compressors.